Exploring the design of technology-mediated nudges for online misinformation - Konstantinou, Loukas; Panos, Dionysis; Karapanos, Evangelos (My University, 2024)
Interest in technological solutions for combating online misinformation has rapidly grown over the last decade, yet the majority of proposed tools do not consider behavioral theories in their design, nor have they addressed the ways in which individuals could potentially interact with these tools, while omitting the plausible ways in which variations in the design of the interventions may affect end-users’ decision-making and behavioral responses. In this paper, we explore the potential of nudging to inform the design of technological tools that aim to mitigate online misinformation through behavior change. We report on a design workshop where 29 participants were asked to conceive technology-mediated nudges supporting individuals’ decision-making in the production, dissemination or consumption of misinformative content. In producing novel solutions, participants used the “Nudge Deck,” a design support tool that makes nudge theory, and particularly a framework of 23 interaction design mechanisms for nudging, accessible during time-constrained design meetings. We present the outputs of the session and discuss them in light of prior literature with respect to ethics and potential effectiveness.
Keywords: Nudging; Online misinformation; Behavior change; Cognitive biases